Legates of the Lower Danube Legions of the Roman Empire. A few preliminary remarks - Żyromski, Marek (Balcanica Posnaniensia. Acta et studia, 1990)
The article addresses the problem of legionary legates in the Lower Danube region of the Roman Empire and the possibilities of their prosopographical study. The problem is significant for analyzing the administrative and military structure of the empire. The aim of the work is a preliminary identification of this group of officials and an indication of its research potential. The author applies the prosopographical method, analyzing data on senatorial careers. The most important results indicate that legionary legates formed an important but relatively poorly documented group of officials, occupying a high position in the administrative hierarchy. Their tenure usually lasted about 2.5–3 years, and the office was held between the praetorship and the consulship. The analysis also reveals problems of representativeness of sources and difficulties in reconstructing careers. The conclusion emphasizes the importance of prosopographical studies for understanding Roman elites and the functioning of the state.